The Knowledge, Media and Technology Competencies of the High School Students Receiving Sports Education - Bingölbalı, Abdullah; Karakaya, Yunus Emre (Muş Alparslan Üniversitesi, 2021)
In this research, it was made to reveal the knowledge, media and technology competencies of the students in Sports High Schools. Ethics Committee Report of the Research; It has been taken from the Social and Human Sciences Research Ethics Committee of Fırat University, with the Meeting Number 15 and Decision 7, dated 29.07.2020. The research group consists of 588 randomly selected students who receive sports education in Elazığ, Malatya and Mardin Sports High Schools. “Information, Media and Technology Skills Competence Scale” was used to obtain the data from the research group. Licensed SPSS 22.0 package program was used for data analysis. As a result, a statistically significant relationship was found between independent variables (gender, class, and family income). Among the dependent variables, the highest level of relationship between the scale and its sub-dimensions was found to be positive and moderate between the “Digital Content Development” and “Problem Solving” sub-dimensions (r = 0.587). In the field of sports sciences, it is important that the course contents and curriculum programs are created in a common structure and harmonized with information, media and technology in both secondary and higher education levels.

Bu araştırmada, Spor Liselerindeki öğrencilerin bilgi, medya ve teknoloji yeterliliklerini ortaya koymak amacıyla yapılmıştır. Araştırmanın Etik Kurul Raporu; Fırat Üniversitesi, Sosyal ve Beşeri Bilimler Araştırmaları Etik Kurulu’ndan 29.07.2020 tarih, 15 nolu Toplantı Sayısı ve 7 nolu Kararıyla alınmıştır. Araştırma grubu Elazığ, Malatya ve Mardin Spor Liselerinde spor eğitimi alan ve rastgele yöntemle seçilmiş 588 öğrenciden oluşmaktadır. Araştırma grubundan verileri elde etmek için “Bilgi, Medya ve Teknoloji Becerileri Yeterlilik Ölçeği” kullanılmıştır. Verilerin çözümlenmesinde lisanslı SPSS 22.0 paket programı kullanılmıştır. Sonuç olarak, bağımsız değişkenler arasında (cinsiyet, sınıf ve ailenin gelir durumu) istatistiksel olarak anlamlı ilişki belirlenmiştir. Bağımlı değişkenler arasında ölçek ve alt boyutları arasındaki en yüksek düzeyde ilişkinin “Dijital İçerik Geliştirme” ve “Problem Çözme” alt boyutları arasında (r=0.587) pozitif ve orta düzeyde olduğu tespit edilmiştir. Spor bilimleri alanında gerek ortaöğretim ve gerekse yükseköğretim düzeyinde verilen eğitimlerde, ders içeriklerinin, müfredat programlarının bilgi, medya ve teknolojiyle ortak bir yapıda oluşturulması ve uyum sağlaması önem arz etmektedir.
Spor Eğitimi Alan Ortaöğretim Öğrencilerinin Bilgi, Medya ve Teknoloji Yeterlilikleri